2000
DOI: 10.1074/jbc.m000239200
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoside Transporter Proteins of Saccharomyces cerevisiae

Abstract: These results indicated that FUI1 has high selectivity for uracil-containing ribonucleosides and imports uridine across cell-surface membranes, whereas FUN26 has broad nucleoside selectivity and most likely functions to transport nucleosides across intracellular membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 44 publications
1
45
0
Order By: Relevance
“…In contrast to hENT4, the functional properties of hENT3 have not yet been described. In light of the presence of a long (51 residues), hydrophilic N-terminal region preceding TM1, which possesses a putative dileucine-based targeting motif, we previously suggested that hENT3 might function intracellularly, as is the case for the yeast homologue FUN26 (9,17). In the present study we have confirmed this hypothesis by examining the effect of mutating the targeting motif on the subcellular location of hENT3 and have shown that the transporter is indeed intracellular and partially co-localizes with lysosomal markers.…”
mentioning
confidence: 99%
“…In contrast to hENT4, the functional properties of hENT3 have not yet been described. In light of the presence of a long (51 residues), hydrophilic N-terminal region preceding TM1, which possesses a putative dileucine-based targeting motif, we previously suggested that hENT3 might function intracellularly, as is the case for the yeast homologue FUN26 (9,17). In the present study we have confirmed this hypothesis by examining the effect of mutating the targeting motif on the subcellular location of hENT3 and have shown that the transporter is indeed intracellular and partially co-localizes with lysosomal markers.…”
mentioning
confidence: 99%
“…Together, these results suggest that FUI1, which is a high-affinity uridine permease in S. cerevisiae (30), also is responsible for uridine transport in L. kluyveri. However, in L. kluyveri, there are additional permeases whose functions overlap this function.…”
Section: Discussionmentioning
confidence: 65%
“…Yeast FUN26 and mammalian ENT3 proteins are found on lysosomal membranes where they are thought to be responsible for the release of nucleosides from intracellular compartments following nucleic acid breakdown (30,24). The human ENT4 protein localizes to intracellular vesicles as well as the plasma membrane, and this localization appears to be dynamic (31).…”
Section: Discussionmentioning
confidence: 99%
“…The yeast strain fui1⌬ lacks the high affinity plasma membrane uridine permease Fui1; it is, as a result, deficient in uridine transport and, consequently, resistant to 5-FUrd (30). We used the PfNT2 fcy2 fusion protein to determine whether expression of PfNT2 at the surface of the yeast cell can, by complementation, reverse the 5-FUrd insensitivity seen in fui1⌬ yeast cells.…”
Section: Functional Characterization Of Pfnt2 In Yeast-despite Previomentioning
confidence: 99%